Validation of the Nepalese Version of the Quality of Recovery-15 (QoR-N) Questionnaire in Patients Undergoing Elective Surgery - Chitra Thapa; Sabin Gauchan; Sulav Acharya; Mohan Raj Sharma (Journal of Nepal Medical Association, 2025)
Introduction: The 15-item Quality of Recovery scale is a widely used tool for assessing postoperative recovery. It has been translated and validated in various languages and cultural settings. However, a validated Nepalese version is currently unavailable.